2007
DOI: 10.1111/j.1528-1167.2006.00930.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of EEG Myogenic Artifact with Botulinum Toxin during Video‐EEG Monitoring

Abstract: Summary:Purpose: To determine whether EEG myogenic artifact during video-EEG monitoring (VEM) is reduced with targeted scalp botulinum toxin (BTX-A) injections.Methods: Twelve consecutive patients scheduled for presurgical VEM were treated 2-3 weeks before admission with subcutaneous BTX-A injections at specific EEG electrode locations. On the basis of clinical data available before VEM, four subjects were treated unilaterally (group 1) and eight bilaterally (group 2). BTX-A efficacy was assessed quantitativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…BoNT-A for perioperative pain (Davies et al 2003), treatment for amputation stump-related and phantom-limb pain (Kern et al 2003), plantar fasciitis (Babcock et al 2005), carpal tunnel related-pain (Tsai et al 2006), and even refractory restless-legs syndrome (Rotenburg et al 2006) have been reported. Botulinum toxins may have a role in electrodiagnosis, using BoNT-A pretreatment to reduce electromyographic frontotemporal artifact in electroencephalographic localization of aberrant cerebral discharges (Grant and Hermanowicz 2007). Lastly, direct infusion of botulinum toxin A has been shown in vivo to inhibit enzymes responsible for hippocampal cell death following induced seizures in rats (Manno et al 2007).…”
Section: Future Directionsmentioning
confidence: 99%
“…BoNT-A for perioperative pain (Davies et al 2003), treatment for amputation stump-related and phantom-limb pain (Kern et al 2003), plantar fasciitis (Babcock et al 2005), carpal tunnel related-pain (Tsai et al 2006), and even refractory restless-legs syndrome (Rotenburg et al 2006) have been reported. Botulinum toxins may have a role in electrodiagnosis, using BoNT-A pretreatment to reduce electromyographic frontotemporal artifact in electroencephalographic localization of aberrant cerebral discharges (Grant and Hermanowicz 2007). Lastly, direct infusion of botulinum toxin A has been shown in vivo to inhibit enzymes responsible for hippocampal cell death following induced seizures in rats (Manno et al 2007).…”
Section: Future Directionsmentioning
confidence: 99%
“…Auch auf der Intensivstation lässt sich massives Beißen auf den Tubus oder auf eingeführte Endoskope durch eine Masseterinjektion beheben. Eine ungewöhnliche Vermeidung von EEG-Muskelartefakten ist durch eine botulinumtoxininduzierte Lähmung der verursachenden Muskulatur möglich (7,14).…”
Section: Kompressionssyndrome Und Protektive Indikationenunclassified
“…Similarly, BoNT-A has been used prior to selective peripheral neurotomy in children with spasticity [39]. In adults with epilepsy whose scalp EEG localization of seizures is limited by EMG artefact from contraction of cranial muscles, BoNT-A has been used to diminish artefact and allow seizure localization, a requirement for considering further epilepsy surgery [40,41]. Only in the study by Grant et al [41] was a minor adverse event noted (two patients reported transient difficulty chewing) ( Table 3).…”
Section: Planning For Surgerymentioning
confidence: 99%
“…Only in the study by Grant et al. [41] was a minor adverse event noted (two patients reported transient difficulty chewing) (Table 3).…”
Section: Peri‐operative Indications For Botulinum Toxinmentioning
confidence: 99%